The Effect of Transactional Leadership on Employees Performance - Case Study of 5 Algerian Banking Institutions - Ali Bousbia Brahim; Ognjen Ridic; Tomislav Jukic (Economic Review: Journal of Economics and Business, 2015)
The objective of this study was to determine what managers thought about the organizational results performed by utilizing different leadership styles in a part of the banking sector in Algeria. A quantitative survey instrument was designed to analyze their opinions. Quantitative survey instrument design was adopted as the most cost efficient for this research. Convenience sampling method was utilized. As far as the research time frame was concerned, it was performed in a cross- sectional manner, in the summer of 2014. Out of 174 sent out surveys, the responses were collected from 132 surveyed individuals. The survey was the main instrument for data collection and it was designed in a "5 - point Likert's scale", in addition to descriptive statistics questions. The collected data were analyzed with descriptive statistics. The analysis of variance (ANOVA) was utilized as the tool of inferential statistics in order to determine differences in leadership between multiple groups of respondents, by age groups and employment within the organization. The research was conducted to see how efficiently and effectively managers used available human and other material and financial resources to satisfy customers and achieve organizational goals. The paper investigated the impact of transactional leadership style on employees' performance in Algerian banks. The objectives of the study were to determine the relationship between transactional leadership style and employees performance, The recommendation was made that managers adopt leadership style(s), such as transformational and Level 5 leadership that will enable them to successfully integrate and maximize available resources within the internal and external environment for attainment of organizational goals.
Keywords: M54; 330; Leadership; Transactional Leadership; Organizations; Performance